A Component-Resolved Therapeutic Vaccine for Cockroach Allergy Made of Per a 9 and Transforming Growth Factor-β Homologue, an Immunosuppressive Protein of Brugia malayi - Prangtaworn, Pannathee; Mahasongkram, Kodchakorn; Saeung, Atiporn; Chaisri, Urai; Seesuay, Watee; Reamtong, Onrapak; Tungtrongchitr, Anchalee; Chaicumpa, Wanpen; Sookrung, Nitat (Frontiers in Immunology, 2021)
Allergen-specific-immunotherapy (ASIT) can cause long-term resolution of allergic diseases, reduces drug use and chances of new allergen sensitization. Nevertheless, therapeutic vaccine and data on ASIT efficacy for cockroach (CR) allergy are relatively scarce. In this study, efficacy and mechanism of a novel intranasal vaccine consisting of liposome (L)-entrapped mixture of American CR (Periplaneta americana) major allergen (Per a 9) and immunosuppressive protein of Brugia malayi nematode named transforming growth factor-beta homologue (TGH) in treatment of CR allergy were investigated along with two other vaccines (L-Per a 9 alone and L-TGH alone). All three vaccines could reduce pathogenic type 2 response and lung immunopathology in the vaccines-treated CR-allergic mice, but by different mechanisms. L-Per a 9 caused a deviation of the pathogenic type 2 to type 1 response (IFN--upregulation), whereas the L-(TGH+Per a 9) and L-TGH generated regulatory immune responses including up-expression of immunosuppressive cytokine genes and increment of serum adenosine and lung indoleamine-2,3-dioxygenase-1 which are signatures of regulatory T cells (Tregs) and tolerogenic dendritic cells, respectively. The L-(TGH+Per a 9) should be further evaluated towards clinical application, as this vaccine has a propensity to induce broadly effective therapeutic effects for inhalant allergies.